SIDE EFFECT OF DENTAL CERAMIC DEGRADATION - Sumono, Agus (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
The use of ceramic as the material of denture fabrication is highly desirable because it provides excellent result of final treatment such as hardness resembling to enamel, not easily degraded, esthetically close to genuine color of teeth, stable and translucent. Basically, dental ceramics consist of materials which are generally considered inactive; however, porcelain hides some danger towardthe certain groups of people especially related to dental field such as dentists, dentist assistants, and laboraory groups of people necessarilly contact with the materials used in treatment, sush asceramics. Therefore, these groups are likely contacted with this materials more frequently and in higher dose, thus their risk of side-effect is also greater.